Breaking Tradition: An Exploration of the Historical Relationship Between Theory and Practice in Second Language Teaching - Musumegi Diane (McGraw Hill, 1997)
Breaking Tradition is a fascinating supplement to any language methods course as it analyzes the hotly contested debate between grammar-based approaches to language teaching and more communicative schools of thought. The author's historical framework provides new perspectives on the current debate about approaches to language teaching. The writing style is engaging.